2007
DOI: 10.1063/1.2713176
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-optical and magnetotransport properties of heavily Mn-doped GaMnAs

Abstract: We have studied the magneto-optical and magnetotrasnport properties of Ga 1-x Mn x As thin films with high Mn concentrations (x= 12.2 -21.3%) grown by molecular-beam epitaxy. These heavily Mn-doped GaMnAs films were formed by decreasing the growth temperature to as low as 150-190ºC and by reducing the film thickness to 10 nm in order to prevent precipitation of hexagonal MnAs clusters. Magnetic circular dichroism (MCD) and anomalous Hall effect measurements indicate that these GaMnAs films have the nature of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 22 publications
(10 reference statements)
1
32
0
Order By: Relevance
“…MnAs is not observed in thinner Asrich films ͑7.5 nm͒, which could be below the critical thickness for defect formation. For our As-rich material, we reproduce previously observed limits 5,6 to T C , xx , and film thickness; these limits are overcome by achieving stoichiometry at precise As:Ga.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…MnAs is not observed in thinner Asrich films ͑7.5 nm͒, which could be below the critical thickness for defect formation. For our As-rich material, we reproduce previously observed limits 5,6 to T C , xx , and film thickness; these limits are overcome by achieving stoichiometry at precise As:Ga.…”
supporting
confidence: 69%
“…4 More recently, MBE growth of GaMnAs with x ജ 0.1 was demonstrated in attempts to increase T C . 5,6 These films require reduced T sub ͑Ϸ180°C͒ and are limited to ഛ10 nm thickness; T C 's after annealing reach the previous limit of Ϸ170 K. 4 In these studies, the effect of arsenic flux was not explored, though it should be a critical parameter at these conditions.…”
mentioning
confidence: 99%
“…[1][2][3][4] While these samples have a nominal Mn concentration of about 7%, in samples with higher Mn concentrations, one would expect appreciably higher Curie temperatures T c since the Curie temperatures are for larger concentrations less affected by the percolation effect, which strongly reduces T c for dilute systems. [5][6][7] However, experiments with Mn concentrations of up to 20% show disappointingly low Curie temperatures, [8][9][10][11][12][13] indicating that there is a relatively large concentration of Mn interstitials that can not be removed by annealing. In this paper, we investigate by ab initio calculations the complex diffusion behavior of single Mn interstitials (Mn I ) in Ga 1−x Mn x As samples with higher concentrations of substitutional Mn atoms (Mn S ).…”
Section: Introductionmentioning
confidence: 99%
“…Further T c increase will probably demand increasing Mn content above 10%, accompanied by the sufficiently high concentration of holes. Recently it was reported that uniform GaMnAs can be grown with Mn content of up to 20% [8][9][10], so progress in this direction cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%